2016
DOI: 10.1080/14789450.2016.1205950
|View full text |Cite
|
Sign up to set email alerts
|

Clinical translation of MS-based, quantitative plasma proteomics: status, challenges, requirements, and potential

Abstract: This article reviews the status, challenges, requirements, and potential of translating current, MS-based methods to the clinical laboratory. The described methods are discussed and contrasted within a fit-for-purpose approach, while different resources for quality control, quantitative analysis, and data interpretation are additionally provided. Expert commentary: Although great strides have been made over the past five years in developing reliable quantitative assays for plasma protein biomarkers, it is cruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 115 publications
0
26
0
1
Order By: Relevance
“…Such unparalleled comprehensive proteome profiling will make uDIA assays the method of choice for MS-based protein quantification. The implementation of SRM assays into clinical workflows that has already started [4] will ease the adoption of more highly multiplexed uDIA measurements in clinical analysis. Additional global, inter-laboratory studies investigating reproducibility [83], DIA data processing tools [46] will also contribute to expedite the acceptance of uDIA technologies.…”
Section: Five-year Viewmentioning
confidence: 99%
See 1 more Smart Citation
“…Such unparalleled comprehensive proteome profiling will make uDIA assays the method of choice for MS-based protein quantification. The implementation of SRM assays into clinical workflows that has already started [4] will ease the adoption of more highly multiplexed uDIA measurements in clinical analysis. Additional global, inter-laboratory studies investigating reproducibility [83], DIA data processing tools [46] will also contribute to expedite the acceptance of uDIA technologies.…”
Section: Five-year Viewmentioning
confidence: 99%
“…Biomedical, systems biology, and translational medicine applications of SRM have been recently reviewed [25]. In other recent reviews, Percy et al discussed the challenges, requirements, and strategies for clinical translation of plasma protein biomarkers [4], while Parker et al reviewed the SRM-based biomarker pipeline as it pertains to discovery, verification, and validation studies [5]. Multiplexed SRM technologies have been thoroughly tested in large multi-laboratory studies, such as in a study reported by Abbatiello et al [6] that quantified cancer-relevant proteins across 11 different laboratories and 14 LC-MS systems.…”
Section: Introduction – Data Independent Acquisition For Quantitatmentioning
confidence: 99%
“…While system suitability assessment and experimental design need to be considered for a successful proteomic experiment [2-4], sample cleanup and protein digestion are two primary components of the analysis [1]. Traditional gel-based approaches to prepare samples are laborious and time-consuming [1, 5].…”
Section: Introductionmentioning
confidence: 99%
“…The 96FASP method allows processing multiple samples in parallel while not sacrificing experimental repeatability. Highly parallel sample processing is of particular interest in clinical proteomics or biomarker discovery where large numbers of samples are usually screened to identify candidate markers or potential therapeutic targets [2, 25, 26]. The development of this method offered reliable semi-automated digestion of samples in batches with reduced sample handling, less time to experiment completion when a large batch is processed, and lower cost of shotgun proteomic sample preparation [24].…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews have highlighted the use of MS for the quantitation of proteins in the clinical setting, including strategies for preanalysis, protein digestion, and the use of internal standards (e.g. [12,[22][23][24]); however, these are typically addressing standard MS-based proteomics approaches using triple quadrupole LC-MS/MS instruments. In this perspective, we focus on the advantages of HRAM MS and its potential for translating promising protein biomarkers into diagnostic protein tests.…”
Section: Protein Applications In Clinical Msmentioning
confidence: 99%